Nature-based solutions for circular urban water systems: A scoping literature review and a proposal for urban design and planning. (25th March 2023) - Tsatsou, Alexandra; Frantzeskaki, Niki; Malamis, Simos
Abstract: This article explores eleven types of Nature-based Solutions (NBS) that can contribute to circular systems for water reuse and resource recovery in cities in terms of their function, co-benefits, integration and scaling-up in urban areas. The challenges of urban water management and water scarcity indicate the urgency for the transition to water circularity, and provide an opportunity for integrating NBS in cities. Evidence on the co-benefits of NBS has been gathered in the past 20 years, while applications across the globe provide us with knowledge on their modularity, effectiveness in hybridization and siting in urban environments. This article provides new insights and perspectives compared to published reviews, as it bridges a broad range of disciplinary topics: NBS, non-conventional water sources, circularity, urban design, and urban planning. Based on the scoping literature review of 68 peer-reviewed research articles, four key dimensions for the design and integration of circular water NBS in cities are identified: environmental technology, systems design, urban design, and urban planning. Urban planning can provide the platform to connect evidence on the efficacy and effectiveness of circular water NBS, building on environmental technology knowledge, NBS design innovation, and place-based evidence from NBS applications in urban design. Graphical abstract: Image 1 Highlights: Circular economy is an emerging field for nature-based solutions' applications. Nature-based solutions can reclaim water from non-conventional sources. Nature-based solutions can address water scarcity issues in cities. Four dimensions: environmental technology, systems design, urban design and planning.